The Impact of the SIMASTER Policy on Driving Discipline and Performance: Evidence from Civil Servants in Bungo Regency, Indonesia - Pratama, Adia Rizki; Aripin, Sofjan; Budiman, Rahmat (Manunggal Halim Jaya, 2026)
This study examines the impact of the Integrated ASN (State Civil Apparatus) Management System, SIMASTER (Integrated ASN Management Information System), on the discipline and performance of civil servants in the Regional Government of Bungo Regency, Indonesia. Using a quantitative survey, data were collected from 98 respondents out of a population of 4000 civil servants and analyzed with simple linear regression (SPSS 22). The results show that SIMASTER has a significant impact on discipline (R² = 0.685) and performance (R² = 0.502), while discipline itself has a strong influence on performance (R² = 0.726). Simultaneously, SIMASTER contributed 33% to improvements in both discipline and performance, with the remaining 67% attributed to other factors, including motivation, leadership, and organizational culture. These findings highlight that work discipline is the most dominant factor in shaping civil servant performance. The study concludes that SIMASTER plays a crucial role in promoting accountability and professionalism among civil servants; however, its effectiveness requires reinforcement through training, digital literacy support, and integration with performance-based reward systems.